Inovasi Packaging Produk Sebagai Upaya Peningkatan Daya Jual UMKM Aneka Keripik Pawon Nayla - Umar Abdul Jabbar; Septa Intiar; Ahmad Mansur (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service activity was carried out at the Aneka Keripik Pawon Nayla UMKM located in Blimbing Hamlet, Parakan Village, Rowosari District, Kendal Regency. The main problem faced by partners is that product packaging is still simple and unattractive, only using plain plastic without labels or informative designs. This has an impact on the limited marketing reach and product competitiveness. The purpose of this activity is to increase product selling power by improving packaging design to be more attractive and informative. The implementation methods include: 1) Survey and analysis of existing packaging, 2) Workshop on attractive and informative packaging design, 3) Making a new packaging prototype, 4) Evaluation and refinement of the design. The expected output targets are the creation of a new modern packaging design, increasing product selling value, and publication.